Perencanaan keuangan PT. Luxury Indah Jaya “layanan laundry premium” - Hadinata, Thomas; Aima, Havidz; Syah, Tantri Yanuar Rahmat; Sunaryanto, Ketut (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
Business opportunities are very open, of course they must be able to meet the standards required by the hotel industry. To meet these needs, of course laundry services must have very good planning. This research aims to analyze the financial planning of Luxury Laundry with several measurements such as 1) Financial Report Projections (2) Investment Feasibility Analysis (3) Liquidity Ratios (4) Solvency Ratios (5) Profitability Ratios (6) Activity Ratios. The method used in this research is qualitative method. This research is included in descriptive research because this research aims to describe one incident, namely financial planning at Luxury Laundry. The data source in this research is the financial report at PT Luxury Indah Jaya. Then the instruments used to collect data are observation, interview and documentation instruments. The results of this research show that the NPV value of Luxury Laundry is 12,376 with an IRR of 20.32%. In addition, the rate of return on this investment is 3 years and 8 months. From the results of this research, it can be concluded that the Luxury Laundry business is good enough to be realized.